2013
DOI: 10.2147/ppa.s44413
|View full text |Cite
|
Sign up to set email alerts
|

Use, perceptions, and acceptability of a ready-to-use supplementary food among adult HIV patients initiating antiretroviral treatment: a qualitative study in Ethiopia

Abstract: ObjectivesReady-to-use supplementary foods (RUSF) are used increasingly in human immunodeficiency virus (HIV) programs, but little is known about how it is used and viewed by patients. We used qualitative methods to explore the use, perceptions, and acceptability of RUSF among adult HIV patients in Jimma, Ethiopia.MethodsThe study obtained data from direct observations and 24 in-depth interviews with HIV patients receiving RUSF.ResultsParticipants were generally very motivated to take RUSF and viewed it as ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 22 publications
12
33
0
Order By: Relevance
“…A less sweet-tasting formulation should likely be considered for future uses. LNS was experienced as stigmatizing by only 3 of our study participants; the stigmatizing connotations of LNS were also observed, but not quantified, in Kenya [41] and Ethiopia [46]. Our participants’ (mis)perceptions of LNS as a drug or medicine occurred less frequently than in the Kenyan and Ethiopian studies [41,46].…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…A less sweet-tasting formulation should likely be considered for future uses. LNS was experienced as stigmatizing by only 3 of our study participants; the stigmatizing connotations of LNS were also observed, but not quantified, in Kenya [41] and Ethiopia [46]. Our participants’ (mis)perceptions of LNS as a drug or medicine occurred less frequently than in the Kenyan and Ethiopian studies [41,46].…”
Section: Discussionmentioning
confidence: 50%
“…Sharing of LNS has also been reported in studies in Ethiopia [46] and Malawi [43]. Wherever food sharing is a common practice and even a cultural expectation, as it is in much of sub-Saharan Africa, it is often difficult for participants to not share their supplement, especially with their children.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…RUTF shows promising results in achieving a more prompt restoration of BMI (14,27) and fatfree mass (27) , and is increasingly being used in nutrition supplementation programmes (18) . However, increasing evidence shows that the acceptance of RUTF is low among adult PLHIV (14,17) .…”
Section: Discussionmentioning
confidence: 99%